Implementasi Kebijakan Pemungutan Pajak Atas Transaksi Perdagangan Melalui E-Commerce Di Indonesia - I Kadek Beny; Meilin Loviana Dewi (Universitas Pendidikan Ganesha, 2021)
Tax collection policy is a policy issued by the government in an effort to increase state revenue. Taxes are a taxpayer's obligation or a taxpayer's contribution to a state that is compelling without receiving direct compensation, but the tax is usually allocated to the construction of public facilities and the interests of the government of a country. With the existence of a policy regarding tax collection on trade transactions carried out online, it is hoped that there will be an awareness of taxpayers to carry out their obligations. The types of taxes that can be imposed or collected are the type of income tax (PPh) and the type of value added tax (VAT). With this tax collection policy, it is hoped that it can increase state revenue from the tax sector, especially taxes from online trade transactions by utilizing E-Commerce media. The government through the Directorate General of Taxes (DGT) has confirmed the E-Commerce transaction by issuing SE-62 / PJ / 2013 dated 27 December 2013 concerning the Affirmation of Taxation Provisions on E-Commerce Transactions, which states that there are no new taxes in E-Commerce transactions. commerce. Therefore, the seller or buyer can be taxed in accordance with the applicable tax laws. Taxes on E-Commerce transactions aim to apply justice to all taxpayers, both conventional and E-Commerce.